Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw Terhadap Hasil Belajar Siswa Dalam Pembelajaran Tematik Terpadu Kelas V SDN 02 Aur Kuning Kota Bukittinggi - Vika Bela Putri; Zuardi Zuardi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
This research aims to know the influence of cooperative learning, Jigsaw-type model against the results of student learning in an integrated thematic learning class V SDN 02 Aur Kuning. This type of research is experimental design with true experiment with forms of pretest-posttest control group. The sample of this research was a class V SD 02 Aur Kuning cluster technique based on random selected. The results showed that there were pengaruhmodel cooperative learning outcomes against Jigsaw type of students in learning Thematic Terpadudengan value thitung (-4.1120) > ttabel (1.67155).